Experimental Investigation of Failure Mode and Energy Evolution under Uniaxial Recompression of Granite Predamaged - Yabin Wu; Xiaosheng Liu (Advances in Civil Engineering)
The research work aimed at identifying the failure mode and energy evolution of damaged granite by uniaxial compression tests. The predamage specimens were prepared by cyclic loading with high confining pressure under constant upper and lower cyclic limit loading, which were collected from China. The test results showed that the cyclic loading with high confining pressure does damage to the rock to a certain degree. The macrocracks of predamage rock appear initially when the uniaxial compressive stress reaches 0.8 σmax. The failure mode is mainly mixed by shear failure and tensile failure. There is a critical state of the cyclic test that the predamage rock transforms the brittle deformation into a ductile one during the triaxial compression loading. Before the critical state, the average deformation energy of predamage rock is impacted by confining pressure (strongly, linear negative). The impact energy index and the residual energy of the predamage rock gradually decrease linearly with the increase of confining pressure.